Biochemical profile and protein concentrations of whey from goats and cows in the first 30 days postpartum - Baroza, Paola Fernanda Junqueira [UNESP]; Franciosi, Camila [UNESP]; da Silva, Daniela Gomes [UNESP]; Santana, André Marcos [UNESP]; Fagliari, José Jurandir [UNESP] (Medicina Veterinaria (UFRPE), 2019)
The aim of the study was to determine the biochemical profile and protein concentrations of whey from goats and cows in the first 30 days postpartum. Milk samples from 10 Saanen goats and 10 Holstein cows, that recently gave birth and were healthy, were collected immediately after parturition (D0) and at 1 (D1), 3 (D3), 5 (D5), 14 (D14) and 30 (D30) days postpartum. The IgG concentration, electrophoretic fractionation in agarose film, enzyme activities of alkaline phosphatase (ALP) and gamma-glutamyltransferase (GGT), and albumin, total calcium, iron, phosphorus, magnesium and total protein levels were measured. Between D0 and D3 occurred the main alterations in composition of whey. In whey samples from goats, a decrease of 77.4% and 96.1% in IgG levels measured in D0 (3,889 mg/dL) were noted compared to measurements in D1 (878 mg/dL) and D3 (152 mg/dL). In whey samples from cows, a decrease of 40.0% and 88.6% in IgG levels measured in D0 (7,680 mg/dL) were observed compared to those obtained in D1 (4,609 mg/dL) and D3 (874 mg/dL). Also, a significant gradual decrease in concentrations of alpha globulin, beta globulin, gamma globulin, total protein, albumin, total calcium, iron, phosphorus, magnesium and enzyme activities of ALP and GGT until D30 was found. The knowledge of physiological values of biochemical parameters of whey from goats and cows can be used to evaluate the quality of colostrum and passive immunity transfer and in the diagnosis of mammary gland diseases such as subclinical mastitis.
Perfil bioquímico e proteinograma do soro lácteo de cabras e vacas nos primeiros 30 dias após o parto
Keywords: Colostrum; Enzymes; IgG; Milk; Minerals; Proteins